UTILIZATION SPENT BLEACHING EARTH AS A FILLER OF MATERIAL CONSTRUCTION - Yusnimar Yusnimar; J. N. Rahman; P. Ningendah (Universitas Lambung Mangkurat, 2021)
Spent bleaching earth (SBE) is a waste from cooking oil industry. It is categorized as one of the hazardous and toxic materials, because oil residues in it. Generally, SBE is overcome by landfill and it’s sometimes become problems. Basically SBE contains SiO2 and the size of the grain is very fine, almost the same as the fine aggregate of sand used for making brick. In this study, the making of brick used SBE with several variations (2.75% - 27.52%) of the total raw materials used. Brick making methods are based on SNI 03-0348-1989 for raw material ratio, SNI 03-0348-1989 for molding and presshing, SNI 03-6825-2002 for drying and curing. The brick quality was determined based on fineness modulus parameters, dry weight, brick absorption to water and compressive strength. Brick contain SBE 2.75% was produced with molding size of 15cm x 30cm x 9cm, it has an average dry weight of 7.80 kg, compressive strength of 8.95 MPa and absorbing power of 1.26%.